The Effect of Institutional Ownership, Free Cash Flow, and Asset Structure on Debt Policy with Profitability as a Moderation Variable (Case Study of Property & Real Estate Sector Companies Listed on the IDX for the 2019-2021 Period) - Rizka Rahayu Utami; Sri Wahyuni; Hadi Pramono; Ani Kusbandiyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of institutional ownership, free cash flow, and asset structure on the debt policy of property & real estate companies listed on the IDX during the period 2019 to 2021, moderated by profitability. The sampling technique used was purposive sampling and 45 samples were obtained. The analytical method used is a multiple linear regression test with Moderating Regression Analysis (MRA). The results of the analysis show that asset structure has no impact on debt policy, while institutional ownership and free cash flow have a negative effect. The impact of institutional ownership on debt policy can be moderated by profitability. However, profitability cannot moderate the impact of free cash flow and asset structure on debt policy.